2016
DOI: 10.1111/jdv.13959
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia areata totalis and universalis: a multicenter review of 132 patients in Spain

Abstract: Treatment of AAT and AAU is challenging. Although an initial regrowth may be achieved, the duration of response is usually short. There were no significant differences on the effectiveness or duration of response between the various systemic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 44 publications
0
28
1
1
Order By: Relevance
“…Age of onset of AT/AU was not associated with prognosis. Of note, seven AT/AU patients (5.3%) had spontaneous recovery and five (3.8%) had persistent regrowth after a minimum of 12 months and a median follow‐up time of 14 months …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Age of onset of AT/AU was not associated with prognosis. Of note, seven AT/AU patients (5.3%) had spontaneous recovery and five (3.8%) had persistent regrowth after a minimum of 12 months and a median follow‐up time of 14 months …”
Section: Resultsmentioning
confidence: 99%
“…No gold standard treatment regimen exists in the absence of randomized control trials. Initial recovery rates are often higher than long‐term recovery rates due to the high prevalence of relapse . Jang et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies, performed by Kumar et al, demonstrated a low incidence of DLE in patients with AA, with only one of 104 patients affected. Furthermore, in the study of Vaño‐Galvan, et al . reviewing 132 patients diagnosed with either alopecia areata totalis or universalis, no case with associated DLE was found.…”
mentioning
confidence: 96%